Development Finance : Can Public Private Partnerships cushion the debt crisis in Africa (African Journal of Public Administration & Management, 2026)
Torealizeagenda2063, Governments in Africa are making attempts and, Progressing towards achieving the developed Africa, we want Need for public capital and infrastructure outmatch our capacity. Nonconventional innovation development finance models required annual cost at $1.4 trillion (excluding social protection, large scale water infrastructure, and climate change, adaptation and mitigation (Sustainable Development Solution Network 2015) • Estimated it to be $1.5 trillion –at market prices. (Oxfam ,2015)
Keywords: Development Finance; Public Private Partnerships; debt crisis; Africa